Advanced Computational Methods in Science and Engineering - Koren, Barry; Vuik, Kees.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The aim of the present book is to show, in a broad and yet deep way, the state of the art in computational science and engineering. Examples of topics addressed are: fast and accurate numerical algorithms, model-order reduction, grid computing, immersed-boundary methods, and specific computational methods for simulating a wide variety of challenging problems, problems such as: fluid-structure interaction, turbulent flames, bone-fracture healing, micro-electro-mechanical systems, failure of composite materials, storm surges, particulate flows, and so on. The main benefit offered to readers of the book is a well-balanced, up-to-date overview over the field of computational science and engineering, through in-depth articles by specialists from the separate disciplines.
A Model-Order Reduction Approach to Parametric Electromagnetic Inversion -- Shifted-Laplacian Preconditioners for Heterogeneous Helmholtz Problems -- On Numerical Issues in Time Accurate Laminar Reacting Gas Flow Solvers -- Parallel Scientific Computing on Loosely Coupled Networks of Computers -- Data Assimilation Algorithms for Numerical Models -- Radial Basis Functions for Interface Interpolation and Mesh Deformation -- Least-Squares Spectral Element Methods in Computational Fluid Dynamics -- Finite-Volume Discretizations and Immersed Boundaries -- Large Eddy Simulation of Turbulent Non-Premixed Jet Flames with a High Order Numerical Method -- A Suite of Mathematical Models for Bone Ingrowth, Bone Fracture Healing and Intra-Osseous Wound Healing -- Numerical Modeling of the Electromechanical Interaction in MEMS -- Simulation of Progressive Failure in Composite Laminates -- Numerical Modeling of Wave Propagation, Breaking and Run-Up on a Beach -- Hybrid Navier-Stokes/DSMC Simulations of Gas Flows with Rarefied-Continuum Transitions -- Multi-Scale PDE-Based Design of Hierarchically Structured Porous Catalysts -- From Molecular Dynamics and Particle Simulations towards Constitutive Relations for Continuum Theory.
Keywords: Mathematics; Computer science -- Mathematics; Computer science; Engineering mathematics; Mechanical engineering; Mathematics; Computational Science and Engineering; Computational Mathematics and Numerical Analysis; Appl.Mathematics/Computational Methods of Engineering; Mechanical Engineering; Numerical and Computational Physics